Aedes aegypti Mosquito Potential Larvacidal of Phyllantus niruri L. Leaves Ethanol Extracts - Moh. Lutfi Hasbullah; Yudha Nurdian; Cholis Abrori (Journal of Agromedicine and Medical Sciences, 2019)
Dengue hemorrhagic fever (DHF) is a disease caused by dengue virus transmitted by Aedes aegyptifemale mosquitoes with four major clinical manifestations, such as high fever, hemorrhage,hepatomegaly, and signs of circulatory failure. Indonesia was reported as the 2nd country with thelargest dengue cases among 30 endemic countries. The larvicidal powder is used as one of thedengue virus vector controllers. This study aims to determine the effect of ethanol extract of smallgooseberry leaves (Phyllantus niruri L.) to the death of Aedes aegypti mosquitoes. This study usedquasi experimental method with post test only controlled group design with 1 positive control group(Temephos), 1 group of negative control (tap water), and 5 treatment groups (0.0625%, 0.125%,0.25% , 0.5% and 1% extract) used 20 larvaes of Aedes aegypti instar III each group. The results of thetreatment group extract with a concentration of 0.5% and 1% obtained 100% dead larvae. The resultof linear regression test showed the effect of meniran leaf extract on the death of larvae Ae. aegyptiwith R2 value of 65.2%. The larvacid activity of ethanol extract leaves meniran against larvae Ae.aegypti instar III was directly proportional to concentration with LC50 of 0.174% with 95% confidenceinterval (0.155-0.195).